Strategi Public Relations Qubic Ball Dalam Membangun Identitas Digital Agency - Rara Aftitah (Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to describe the public relations strategy of Qubic Ball in building the agency's digital identity. The theory used in this research is the theory of public relations. The research method used in this research is a descriptive qualitative method. Data collection techniques were interviews and documentation obtained by two informants in the study. The informants in this study were the owner and public relations of Qubic Ball. The data analysis technique used in this research is to collect data, reduce data, conclude and verify. The results show that Qubic Ball's public relations strategy in building a digital agency identity is to do the Four Step Model of Public Relations, namely defining the problem (defining public relations), planning and programming (planning and programming), taking action and communicating (taking action and communicating). Communicating), and evaluating the program (evaluating the program). Several things that make a positive contribution to the identity of a company are an inspiring vision, name and logo, and consistency that have managed to maintain the digital agency identity that has been built for a long time.